Antioxidant Enzyme Responses in Cladoceran Moina macrocopa under Oxidative Stress - Dongare, Veena; Pandey, Shahshibhal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Oxygen is the cornerstone of the life of all living organisms, as it plays a pivotal role in regulating the bio-physiological functions of the organism that are necessary to sustain its existence. Oxidative stress/ hypoxia is a condition of inadequate oxygen that disrupts the harmony of an organism's life by impairing its growth, puts the organism's survival at risk, and destabilizes the ecosystem. Like all other organisms Moina, a small cladoceran is susceptible to the alteration in dissolved oxygen levels. Here we report that, in response to hypoxia, Moina adjusts their antioxidant enzyme activities as a mechanism of adaptation. Significant changes were observed in the levels of LDH, GST, and SOD antioxidant enzymes of Moina under hypoxia (p=0.001053, GST p=0.0010053, SOD p=0.0015). These results can contribute to wider research on environmental stress tolerance by aquatic organisms and will assist in the conservation of species like Moina. Moina, being an ecological indicator, this research will help in environmental monitoring using it as a model organism.